2014
DOI: 10.3349/ymj.2014.55.6.1712
|View full text |Cite
|
Sign up to set email alerts
|

Does Age at Onset of First Major Depressive Episode Indicate the Subtype of Major Depressive Disorder?: The Clinical Research Center for Depression Study

Abstract: PurposeThe purpose of this study was to evaluate the effects of age at onset of the first major depressive episode on the clinical features of individuals with major depressive disorder (MDD) in a large cohort of Korean depressed patients.Materials and MethodsWe recruited 419 MDD patients of age over 18 years from the Clinical Research Center for Depression study in South Korea. At the start of the study, the onset age of the first major depressive episode was self-reported by the subjects. The subjects were d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 65 publications
(34 citation statements)
references
References 33 publications
1
33
0
Order By: Relevance
“… 51 Besides, a recent study has demonstrated that early age at onset may increase the likelihood of distinguishable MDD subtype, and age at onset of the first episode MDD is a promising clinical indicator for the clinical presentation, course, and outcome of MDD. 52 To better explore the neuroanatomical characteristics of depression and anxiety disorders, it would be useful to recruit drug-naive, first-episode patients of depression and anxiety disorders in the future study. Second, the results of our VBM analyses were inconsistent with many previous studies.…”
Section: Discussionmentioning
confidence: 99%
“… 51 Besides, a recent study has demonstrated that early age at onset may increase the likelihood of distinguishable MDD subtype, and age at onset of the first episode MDD is a promising clinical indicator for the clinical presentation, course, and outcome of MDD. 52 To better explore the neuroanatomical characteristics of depression and anxiety disorders, it would be useful to recruit drug-naive, first-episode patients of depression and anxiety disorders in the future study. Second, the results of our VBM analyses were inconsistent with many previous studies.…”
Section: Discussionmentioning
confidence: 99%
“…Those with MDD who also have psychotic symptoms or a family history of psychotic illness likely index individuals with more severe forms of MDD (Park et al, 2014;Parker et al, 2013).…”
Section: Psychiatric Outcomesmentioning
confidence: 99%
“…similar mean age has been found in multiple studies. [23][24][25] The mean age of onset of illness of depression with suicidal behaviour patients was 32.6±11.90 years, previous studies have found mean age of onset to be around 39±5 years. 26 Depression without suicidal behaviour patients had a mean HAM-D score of 15.28±2.80 equivalent of moderate depression while depression with suicidal behaviour patients had a mean HAM-D score of 20.36±7.04 which corresponds to severe depression as per HAM-D (Table 2).…”
Section: Discussionmentioning
confidence: 99%